Peran Komite Sekolah dalam Meningkatkan Kulitas Pendidikan di SDN 05 Pandan Wangi: The Role of the School Committee as a Mediator Between Parents and the School in Improving the Quality of Education at SDN5 Pandan Wangi - Abd Quddus al Badani; Sapruddin Effendi; Ade Maharani; Agus Mantohri; Ahmad Pramuja Wijaya (Pendidikan Al-Gafari, 2026)
The Role of the School Committee as a Mediator in Improving the Quality of Education at SDN 5 Pandan Wangi This study aims to understand the role of the school committee as a mediator between parents and the school in improving the quality of education at SDN 5 Pandan Wangi. A qualitative approach with a case study method was chosen to explore in depth the dynamics of interaction and influence of the school committee in the specific context of the school. This study is expected to provide recommendations for SDN 5 Pandan Wangi to improve the role of the school committee in improving the quality of education, as well as provide a better understanding of the role and function of the school committee for parents and the school. In addition, this study is expected to contribute to the development of knowledge about the role of the school committee in improving the quality of education in Indonesia.